Birth Weight and Labor Market Outcomes: Findings From Tohoku Medical Megabank Data - Midori Matsushima; Taku Obara; Mami Ishikuro; Naoki Nakaya; Atsushi Hozawa; Shinichi Kuriyama (Wiley, 2024)
ABSTRACT Background Epidemiological and economic literature has revealed that low birth weight (LBW) is related to poor health conditions and a broader range of negative socio‐economic outcomes, including academic achievement, income levels, and working status. However, Japanese evidence for labor outcomes is particularly lacking, as is the question of whether the impact of LBW on adulthood worsens when disasters occur. We aimed to reveal the impact on LBW on labor outcomes during the disaster recovery phase. Methods We used a cross‐sectional data set of 4156 national health insurance holders, males aged 40-60 years, from the Miyagi and Iwate prefectures during the earthquake recovery phase. Employing a multinomial probit and logistic model, we estimated the impact of LBW on the employment status, changes in income, and the propensity to face a decline in income with a job change. Results The very low birth weights (VLBWs) have a disadvantage in all labor market outcomes. Compared to the non‐LBWs, the VLBWs were 15.2% less likely to be full‐time/self‐employed and 17.1% more likely to be contingent/temporary/part‐time workers. Moreover, 32.9% are more likely to face a decline in income and approximately 3.7 times more likely to change jobs leading to income decline. The LBWs were likely to face a decline in income by 8.6% and 4.6%, respectively, but no other significant effects were found on other outcomes. Conclusions The effects were apparent for the VLBW, but not so much for the LBW. The effects became larger during the disaster recovery phase, even though the regional economies were boosted.